2013
DOI: 10.3389/fnsys.2013.00006
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct-current stimulation increases extracellular dopamine levels in the rat striatum

Abstract: Background: Transcranial direct-current stimulation (tDCS) is a non-invasive procedure that achieves polarity-dependent modulation of neuronal membrane potentials. It has recently been used as a functional intervention technique for the treatment of psychiatric and neurological diseases; however, its neuronal mechanisms have not been fully investigated in vivo.Objective/Hypothesis: To investigate whether the application of cathodal or anodal tDCS affects extracellular dopamine and serotonin levels in the rat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 68 publications
(91 reference statements)
4
68
1
2
Order By: Relevance
“…The stimulation of dopaminergic neurons increases locomotor activity (Fishman et al, 1983), which proves the importance of these neurons to the modulation of this behavior. The use of tDCS in humans is known to increase the levels of extracellular dopamine (Tanaka et al, 2013). Arguably, then, tDCS treatment modulates the dopaminergic system in the frontal cortex, promoting dopamine release and consequently improving locomotor and exploratory activities of CCI rats.…”
Section: Discussionmentioning
confidence: 98%
“…The stimulation of dopaminergic neurons increases locomotor activity (Fishman et al, 1983), which proves the importance of these neurons to the modulation of this behavior. The use of tDCS in humans is known to increase the levels of extracellular dopamine (Tanaka et al, 2013). Arguably, then, tDCS treatment modulates the dopaminergic system in the frontal cortex, promoting dopamine release and consequently improving locomotor and exploratory activities of CCI rats.…”
Section: Discussionmentioning
confidence: 98%
“…The motor deficit of Parkinson's disease can be influenced by tDCS applied parallel over the motor and prefrontal area [20]. Similarly to the rTMS, one of the supposed sites of action of tDCS -according to animal studies -is the dopamine release in the striatum [21]. These promising results urge the involvement of non-invasive brain stimulation in the treatment of Parkinson's disease because the respond for dopaminergic therapy is less effective over years.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 96%
“…Notably, Monti et al reported that cathodal tDCS of Wernicke's area, as opposed to anodal tDCS, enhanced the performance of aphasic patients in a picture-naming task [ 69 ]. In animal models, tDCS appears to infl uence motivation and reward systems [ 70 ] and thus has been suggested to alter preference and/or craving behaviors. Bilateral frontal cortical tDCS altered preference in patients with addictive disorders and reduce cravings for alcohol [ 71 ], smoking [ 72 ], and even for specifi c foods [ 73 ].…”
Section: Transcranial Direct Current Stimulation and Behavioral Changmentioning
confidence: 98%